ANALISIS INSTRUMEN PENILAIAN GURU SEBAGAI UPAYA MENINGKATKAN KUALITAS EVALUASI PEMBELAJARAN SEKOLAH DASAR SDN 5 METRO UTARA - Hendri Pratama; Savira Aulia Putri; Anindita Khailasyah; Novi Susanti; Astri Widya Utami; Handoko (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze teacher assessment instruments as an effort to improve the quality of learning evaluation at SDN 5 Metro Utara. This study employed a qualitative approach with a descriptive method. The research subjects were elementary school teachers involved in the preparation and implementation of assessment instruments. Data were collected through observation, interviews, and documentation. The data analysis technique consisted of data reduction, data presentation, and conclusion drawing. The findings showed that the assessment instruments used by teachers covered cognitive, affective, and psychomotor aspects. However, several obstacles were still found in their implementation, such as teachers’ difficulties in developing assessment indicators aligned with learning outcomes and the limited development of skill-based assessment instruments. In addition, learning evaluation had been carried out continuously to monitor students’ learning progress. Therefore, the analysis of teacher assessment instruments plays an important role in improving the quality of learning evaluation in elementary schools.